ANALISIS PENGARUH NPM, ROA, UKURAN PERUSAHAAN DAN FINANCIAL LEVERAGE TERHADAP PRAKTIK PERATAAN LABA (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2008-2011) - Dyah Astuti, Sahening; Tri Widyarti, Endang (Diponegoro Journal of Management, 2013)
Income smoothing is used by management of manufacture companies to make companiesincome stable and not fluctuate over several periode. The aim of this study is to examine theinfluence of NPM, ROA, size of the company, and, financial leverage toward practice of incomesmoothing among manufacture companies listed on the Indonesian Stock Exchange. This studyuses eckel index to classify companies that do or do not practice income smoothing.The sample used in this study is 74 manufacturing companies listed on the IndonesianStock Exchange within a period of four years beginning in 2008 until 2011 with the selectionmethod of purposive sampling. Statistical analysis used in this study uses descriptive statistics, andlogistic regression models through multivariate testing.The results of eckel index showed practice of income smoothing by manufacturingcompanies listed on the Indonesian Stock Exchange. Based on the result of logistic regression forthe four independent variables, only financial leverage that have a significant effect on the practiceof income smoothing while the NPM, ROA and size of the company does not significantly influencethe practice of income smoothing.